Penyimpanan Awan Sebagai Penyimpanan Digital Bagi Santri Pesantren Tahfidz Quran As-Sholah Gunung Sindur Bogor - Cholis Hanifurohman; Rengga Herdiansyah; Debby Rahadian Baskhara (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In realizing one of the lecturer's tasks, namely the Tri Dharma of higher education at Pamulang University, the team of service lecturers carried out Community Service activities (PKM). Community Service is carried out as a service to the community in the form of the application of science and technology so as to contribute and progress to society. This community service is entitled "Cloud Storage as Data Storage for Students at the Tahfidz Quran Islamic Boarding School As-Sholah Gunung Sindur Bogor". The methods used are lectures, discussions and training. As a result of this community service activity, students have started using cloud storage as an alternative storage besides paper, laptop hard drives for storing letters, activity certificates, important photos and so on. The output to be achieved in this community service is a national journal.